EGFR testing patterns and detection of EGFR exon 20 insertions among patients with NSCLC in the US. (28th October 2021) - Lin, H M; Yin, Y; Curran, E; Crossland, V; Wu, Y; Ou, S
Abstract: Introduction/Objective: Epidermal growth factor receptor (EGFR) mutations are common in non-small cell lung cancer (NSCLC). EGFR exon 20 insertions (EGFRex20ins), a rare subset of EGFR mutations, are refractory to tyrosine kinase inhibitors. With the development of targeted therapies for EGFRex20ins, such as mobocertinib, molecular testing is required to optimize treatment. A better understanding of real-world EGFR detection patterns is needed to maximize patient outcomes. Methods/Case Report: This retrospective study describes EGFR testing and EGFRex20ins detection patterns in patients with NSCLC in the United States. The Flatiron Health electronic health record database was used to identify patients ≥18 years, with advanced NSCLC, and with ≥2 clinic visits between 01/01/2011 and 12/31/2020. Baseline demographics, clinical characteristics, EGFR testing, and EGFRex20ins detection rates by sex, race, and smoking history were summarized. Results (if a Case Study enter NA): A total of 67, 281 patients with NSCLC were identified. EGFR testing increased from 44% in 2011 to 77% in 2020. Of all patients, 44, 926 (66.8%) were tested: 50.8% female; 3.3% Asian; 16.0% never-smokers. Of all patients, 22, 355 (33.2%) were not tested: 41.4% female; 1.2% Asian; 7.5% never-smokers. Of those tested, 6, 245 (13.9%) patients had EGFR mutations: 65.9% female; 11.8% Asian; 48.4% never-smokers. EGFRex20ins detection rates changed from 0.6% in 2011 to 1.0% in 2019 and 0.7% in 2020. Of those tested, 304 patients had EGFRex20ins: 58.2% female; 8.2% Asian; 50.3% never-smokers. EGFR testing was higher in females (71.2%) than males (62.8%), never-smokers (84.5%) than those with a smoking history (64.6%), and Asian patients (84.2%) than White (66.6%), Black (65.4%), or other patients (69.5%). Of those tested, EGFRex20ins mutations were detected in 0.8% of females (males: 0.6%), 2.2% of never-smokers (with smoking history: 0.4%), and 1.7% of Asians (White: 0.6%, Black: 0.6%, other patients: 0.7%) had EGFRex20ins. A similar trend was observed for EGFR mutations with higher proportions of females, never-smokers, and Asian patients affected. Conclusion: EGFR testing and EGFRex20ins detection rates have increased. However, not all patient subgroups were tested at the same rate and undertesting occurred in all subgroups. Further education of specialists diagnosing NSCLC is warranted to ensure all patients receive biomarker testing and benefit from emerging EGFRex20ins- targeted therapies.